(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
On August 25th, 2010, four specimens of the invasive lionfih Pterois volitans were seen inhabiting the submerged roots of mangroves bordering the entrance to the southern lagoon of Bahía de Chengue, at the Parque Nacional Natural Tayrona. One specimen (40 mm total length) was captured and photographed. The occurrence of this deleterious fih in such an ecological and economic valuable ecosystem is considered potentially dangerous.